Acyclovir Induced Acute Kidney Injury: A Case Report - Mohammed, Ziauddin; Muskan, Mariya Zoha; Narayanan, Megha Mohan (Archives of Pharmacy and Pharmaceutical Sciences, 2024)
Herpes zoster ophthalmicus, commonly referred to as shingles, manifests as a painful skin rash affecting one or more dermatome distributions of the trigeminal nerve, which supplies sensory innervation to the eye and its surrounding structures. Acyclovir stands as the primary pharmacological intervention for the treatment of this condition. However, its administration is associated with a notable risk of adverse effects, with acute kidney injury being the most prevalent. Herein, we present a case report involving a 59-year-old female patient who developed acute kidney injury after the prescription of Acyclovir for the management of herpes zoster ophthalmicus. This case underscores the importance of vigilance regarding potential renal complications associated with Acyclovir therapy, particularly in susceptible patient populations.